Dominant factors that determine college students completing studies in mathematics education study programs - Dewanti, Sintha Sih; Pramono, Aji Joko Budi (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
Failure to graduate on time is a problem for both the university and the students themselves. Beside the competencies possessed by students, many other factors affect the completion of student studies. This study aims to reduce the variables that really affect the completion of student studies. The approach of this research was survey research on students of the Mathematics Education Study Program at least in semester 7 (currently taking a final project course). There are 17 factors that determine the completion of student studies, namely achievement motivation, discipline, interest, intelligence, study habits, health, part-time work activities, organizational activities, curriculum, mentoring methods, student relations with lecturers, availability of books, internet facilities, family economic conditions, relationships with parents and family members, friends, and social environment. Data analysis was conducted using Principal Component Analysis (PCA) method to obtain the dominant factor. Based on the results of the study, four main factors that affect the completion of student studies are formed, namely: (1) the first factor: motivation and academic ability; (2) the second factor: activities and social environment; (3) the third factor: facilities and family; and (4) the fourth factor: thesis guidance. The four factors can explain the dominant factor in student study completion at 86.54%, with details of motivation and academic ability at 37.57%, activities and social environment at 26.34%, facilities and family at 15.21%, and thesis guidance at 7.42%.